Field evaluation of a schistosome circulating cathodic antigen rapid test kit at point-of-care for mapping of schistosomiasis endemic districts in The Gambia. - Bakary Sanneh; Ebrima Joof; Abdoulie M Sanyang; Kristen Renneker; Yaya Camara; Alhagie Papa Sey; Sheriffo Jagne; Ignatius Baldeh; Serign Jawo Ceesay; Sana M Sambou; Kisito Ogoussan (PLoS ONE)
Background Studies in Sub Saharan Africa have shown that the Circulating Cathodic Antigen point-of-care-test (POC-CCA) is more accurate in the detections of S. mansoni than the microscopic Kato-Katz technique but less is known about the accuracy of this rapid test in detecting S. haematobium infections. This study was intended to evaluate the field accuracy of POC-CCA as a rapid test kit for schistosomiasis mapping in The Gambia. Methods This prospective study was conducted in 4 regions in the country. Ten schools were randomly selected from each region, and a total of 2018 participants whose ages range from 7 to 14 years were enrolled in the study. Stool and urine samples were collected from each participant from May to June 2015, and tested for S. haematobium and S. mansoni infections in field and laboratory settings. The tests conducted included POC-CCA, double Kato-Katz slides, urine filtration and dipstick for hematuria. Results Of the 1954 participants that had complete data, the mean age of participants was 9.9 years. The prevalence of children infected with S. haematobium, using urine filtration technique was 10.1% (95% CI: 8.87-11.55). Central River Region had the highest level of urinary schistosomiasis with a prevalence of 28.0% (24.13-32.12).The lowest urinary schistosomiasis prevalence of 0.6% (0.12-1.86) was found in Lower River Region and North Bank Region had no cases of schistosomiasis detected. Only 5 participants were infected with S. mansoni. Using urine filtration as reference standard for the detection of S. haematobium, the sensitivity and specificity of POC-CCA was 47.7% and 75.8%. Whilst sensitivity and specificity of POC-CCA for detecting S. mansoni were 60.0% and 71.2% using double Kato-Katz as reference standard. Conclusion This study showed lower sensitivity of POC-CCA in detecting S. haematobium. Therefore POC-CCA is less useful for rapid diagnosis of urinary schistosomiasis.